2012
DOI: 10.1111/j.1439-0531.2012.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (−)‐Epigallocatechin Gallate on the Motility and Penetrability of Frozen–Thawed Boar Spermatozoa Incubated in the Fertilization Medium

Abstract: Epigallocatechin gallate (EGCG) is the major polyphenol in green tea (Camellia sinensis) and is known for its antioxidant effects. The objective of the present study was to examine the effects of EGCG during in vitro fertilization (IVF) on the sperm quality and penetrability into oocytes. In the first experiment, the effects of concentration and incubation period of EGCG on the motility and penetrability of spermatozoa were examined. When frozen-thawed spermatozoa were incubated in IVF medium supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…produced significant improvement in total motility and reduced the lipoperoxidation on boar spermatozoa (Zhao et al ., ; Malo et al ., ). Epigallocatechin gallate (the major polyphenol in green tea) and rosmarinic acid (the main antioxidant in rosemary) improved the motility and penetrability of frozen–thawed boar spermatozoa (Kaedei et al ., ; Luño et al ., ). Recently, studies showed that essential oil of geranium ( Pelargonium graveolens) prevented testicular oxidative damage by reduced lipoperoxidation and improved total sperm motility, viability and morphology in mice spermatozoa after administration of reprotoxic drug (Slima et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…produced significant improvement in total motility and reduced the lipoperoxidation on boar spermatozoa (Zhao et al ., ; Malo et al ., ). Epigallocatechin gallate (the major polyphenol in green tea) and rosmarinic acid (the main antioxidant in rosemary) improved the motility and penetrability of frozen–thawed boar spermatozoa (Kaedei et al ., ; Luño et al ., ). Recently, studies showed that essential oil of geranium ( Pelargonium graveolens) prevented testicular oxidative damage by reduced lipoperoxidation and improved total sperm motility, viability and morphology in mice spermatozoa after administration of reprotoxic drug (Slima et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…When stallion spermatozoa were treated under capacitating condition with 10 and 20 lM EGCG, stallion sperm-ZP binding activity was improved compared with control semen. A positive influence of EGCG addition on both fresh and frozen-thawed spermatozoa during IVF on ZP binding and oocyte penetration was already recorded in pig (Spinaci et al 2008;Kaedei et al 2012), suggesting a modulating action of this polyphenol on sperm capacitation. This effect could be exerted thanks to the antioxidant ability of EGCG that can act on the balance between excessive ROS production, which overwhelms the limited capacity of these cells to protect themselves from oxidative stress, and mild intracellular ROS generation, which stimulates intracellular cAMP generation, inhibits tyrosine phosphatase activity and enhances the formation of oxysterols, thus inducing a physiological capacitation (Aitken et al 2015).…”
Section: Discussionmentioning
confidence: 85%
“…; Kaedei et al. ), suggesting a modulating action of this polyphenol on sperm capacitation. This effect could be exerted thanks to the antioxidant ability of EGCG that can act on the balance between excessive ROS production, which overwhelms the limited capacity of these cells to protect themselves from oxidative stress, and mild intracellular ROS generation, which stimulates intracellular cAMP generation, inhibits tyrosine phosphatase activity and enhances the formation of oxysterols, thus inducing a physiological capacitation (Aitken et al.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, Kaedei et al (2012) reported that EGCG (50 μmol/L) has positive effects on sperm penetration rates and sperm motility when frozen-thawed boar spermatozoa are incubated in IVF medium supplemented with various amounts of EGCG. Among them, EGCG is abundantly present.…”
Section: Results and Discussion Experiments 1: Effects Of Pre-treatmenmentioning
confidence: 99%